Monoclonal Antibodies B38 and H4 Produced in Nicotiana benthamiana Neutralize SARS-CoV-2 in vitro - Shanmugaraj, Balamurugan; Rattanapisit, Kaewta; Manopwisedjaroen, Suwimon; Thitithanyanont, Arunee; Phoolcharoen, Waranyoo (Frontiers in Plant Science, 2020)
The ongoing coronavirus disease (COVID-19) outbreak caused by novel zoonotic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was initially reported in Wuhan city, Hubei Province of China, in late December 2019. The rapid global spread of the virus calls for the urgent development of vaccines or therapeutics for human applications to combat coronavirus infection. Monoclonal antibodies (mAbs) have been utilized as effective therapeutics for treating various infectious diseases. In the present study, we evaluated the feasibility of plant expression system for the rapid production of recently identified therapeutically suitable human anti-SARS-CoV-2 mAbs B38 and H4. Transient co-expression of heavy chain and light chain sequences of both the antibodies by using plant expression geminiviral vector resulted in rapid accumulation of assembled mAbs in Nicotiana benthamiana leaves within 4 days post-infiltration. Furthermore, both the mAbs were purified from the plant crude extracts with single‐step protein A affinity column chromatography. The expression level of mAb B38 and H4 was estimated to be 4 and 35 μg/g leaf fresh weight, respectively. Both plant-produced mAbs demonstrated specific binding to receptor binding domain (RBD) of SARS-CoV-2 and exhibit efficient virus neutralization activity in vitro. To the best of our knowledge, this is the first report of functional anti-SARS-CoV-2 mAbs produced in plants, which demonstrates the ability of using plant expression system as a suitable platform for the production of effective, safe and affordable SARS-CoV-2 mAbs to fight against the spread of this highly infectious pathogen.